PERANCANGAN SISTEM KONTROL MOBIL MENGGUNAKAN COMPRESSED AIR ENGINE SEBAGAI PENGGERAK MULA - Sumadi, Sumadi; Sutisna, Setya Permana (UNIVERSITAS IBN KHALDUN BOGOR, 2019)
This research is an initial research in the development of cars with compressed air engine drivers. Modifications are made to the engine of 2-stroke motorized vehicles fueled by gasoline. Pressurized actuators using selenoid valves are ordered based on the piston position obtained from the proximity sensor. When the proximity sensor detects the piston is in the TMA position, the selenoid valve is ordered to open so that pressurized air enters the combustion chamber and pushes the piston to move to the TMB and turns back to TMA. The selenoid valve will close again when the proximity sensor detects that the piston is moving from TMA to TMB. Pressurized air is given to move the piston to produce a spin on the wheel. Air pressure is given at 0.92 bar to 2.36 bar resulting in a maximum rotating speed of 1035 rpm, torque of 1.33 Nm, and maximum power of 0.71 kW based on the results of static testing. This research will continue to be developed to optimize the torque and power produced so that cars driven by compressed air engines can be produced.